Inter-joint coordination changes during walking in typically developing children: the vector coding analysis - Mochizuki, Luis (2024)
BACKGROUND: Coordination is the key to developing biomechanical gait patterns. AIM: To describe the coordination modes during walking in 5-to-10-years-old typically developing children using the vector coding analysis. METHOD: 11 boys and 17 girls were divided into three groups according to their ages. Joints of the right lower limb kinematics were analyzed during walking. The coupling angle was calculated using vector coding analysis to describe the inter-joint coordination by the coordination modes. RESULTS: Results indicated significant differences in coordination modes based on the stance subphase and age group. The in-phase mode duration increased in the late stance, while the anti-phase mode varied more across subphases and groups. Proximal and distal modes also showed differences, with variability and predominant coordination strategies analyzed across groups. CONCLUSION: Changes in inter-joint coordination were mostly related to the mid-stance phase. Its variability decreased as children were older. Motor development seems to move towards an optimal for walking, suggesting older children control more than one joint at the same time using parallel coordination.